Circulating tumor cells and miRNAs as prognostic markers in neuroendocrine neoplasms. Issue 6 (June 2017) - Zatelli, Maria Chiara; Grossrubatscher, Erika Maria; Guadagno, Elia; Sciammarella, Concetta; Faggiano, Antongiulio; Colao, Annamaria
Abstract : The prognosis of neuroendocrine neoplasms (NENs) is widely variable and has been shown to associate with several tissue- and blood-based biomarkers in different settings. The identification of prognostic factors predicting NEN outcome is of paramount importance to select the best clinical management for these patients. Prognostic markers have been intensively investigated, also taking advantage of the most modern techniques, in the perspective of personalized medicine and appropriate resource utilization. This review summarizes the available data on the possible role of circulating tumor cells and microRNAs as prognostic markers in NENs.